Enhanced optical and electrochemical properties of FeBTC MOF modified TiO2 photoanode for DSSCs application - William Moloto; Pontsho Mbule; Edward Nxumalo; Bulelwa Ntsendwana (Scientific Reports, 2024)
Abstract In this work, iron based 1, 3, 5-tricarboxylic acid (FeBTC) was prepared via microwave-assisted method and incorporated into TiO2 via ultrasonic assisted method. The TiO2–FeBTC nanocomposites were characterized by XRD, FTIR, Raman, BET, FESEM, HRTEM, TGA, UV‒vis DRS and PL to understand their crystallographic, surface morphology, and optical characteristics. The Raman spectra showed a blue shift of Eg, A1g, and B1g peaks upon incorporation of FeBTC MOF onto TiO2. HRTEM and XRD analysis confirmed a mixture of TiO2 nanospheres and hexagonal FeBTC MOF morphologies with high crystallinity. The incorporation of FeBTC onto TiO2 improved the surface area as confirmed by BET results, which resulted in improved absorption in the visible region as a results of reduced bandgap energy from 3.2 to 2.84 eV. The PL results showed a reduced intensity for TiO2–FeBTC (6%) sample, indicating improved separation of electron hole pairs and reduced recombination rate. After fabrication of the TiO2–FeBTC MOF photoanode, the charge transfer kinetics were enhanced at TiO2–FeBTC MOF (6%) with Rp value of 966 Ω, as given by EIS studies. This led to high performance due to low charge resistance. Hence, high power conversion efficiency (PCE) value of 0.538% for TiO2–FeBTC (6%) was achieved, in comparison with other loadings. This was attributed to a relatively high surface area which allowed more charge shuttling and thus better electrical response. Conversely, upon increasing the FeBTC MOF loading to 8%, significant reduction in efficiency (0.478%) was obtained, which was attributed to sluggish charge transfer and fast electron–hole pair recombination rate. The TiO2–FeBTC (6%) may be a good candidate for use in DSSCs as a photoanode materials for improved efficiency.